Cross-sectional investigation and correlation analysis of psychology of college students returning to campus after COVID-19 lockdown lift - Wang, Zhifeng; Jiang, Bing; Wang, Xingtong; Niu, Yi; Xue, Haihong (Frontiers in Psychiatry, 2022)
ABSTRACT: Objective: To conduct a large cross-sectional survey of the mental health of college students during the recovery period of the COVID-19 epidemic. Methods: Symptom Checklist 90 (SCL-90) and COVID-19 questionnaire were used to investigate the overall mental health level and cognition of epidemic situation of college students in 7 colleges and universities in Shaanxi Province. Results: (1) In the recovery period of COVID-19 epidemic, college students still had psychological and somatic symptoms such as obsessive-compulsive disorder, interpersonal sensitivity, anxiety, hostility, and poor appetite or insomnia; (2) female college students, science and engineering college students, freshmen and senior graduates, and some ethnic minority college students were all groups with psychological symptoms; (3) The psychological status of college students was related to their perception of COVID-19 epidemic, and the more knowledge about epidemic prevention and control, the more confident they were in overcoming the epidemic, and the milder the psychological symptoms. Conclusion: College students still have some mental health problems in the recovery period of COVID-19 epidemic, which should be paid attention to by education authorities and colleges and universities.